PENGARUH KREATIVITAS MENGAJAR GURU SOSIOLOGI TERHADAP PRESTASI BELAJAR SISWA - Fransisco Emiliano Wololele; Nur Wahida Yusuf (Prosiding Ilmu Pendidikan dan Keguruan, 2026)
This study aims to analyze the effect of sociology teachers' teaching creativity on students' learning achievement at SMA PGRI Lewoleba. The research employed a quantitative, correlational approach. Data were collected through observation, questionnaires, interviews, and documentation. The sample consisted of 30 students randomly selected from a population of 80. Data analysis was conducted using the product-moment correlation formula. The results showed a positive relationship between teachers' teaching creativity and students' learning achievement, with a correlation coefficient of 0.48, which is considered moderate. These findings indicate that higher teacher creativity in managing the learning process leads to better student achievement. Teacher creativity is reflected in the use of varied teaching methods, engaging learning media, and the ability to create a conducive learning environment. Therefore, enhancing teacher creativity is crucial to improving both the quality of learning and student outcomes.